Potential Reduction of Food Waste and Hospital Wastewater Sludge Using Bioconversion by BSF Larvae - Rafida Aina; Gina Lova Sari; Kania Ratnawati (Jurnal Biologi Tropis, 2026)
Food waste and sludge from the Wastewater Treatment Plant (WWTP) of hospitals are organic wastes with high utilization potential through bioconversion using Black Soldier Fly (BSF) larvae. This study aims to examine the characteristics of food waste and WWTP sludge from Karawang Regional General Hospital and to evaluate their reduction potential through BSF larval activity. The experiment was conducted using three feed variations SML1 (70%:30%), SML2 (50%:50%), and SML3 (30%:70%) along with two control treatments. The analyzed parameters included nutritional content (protein, fat, carbohydrates, ash content, moisture content, and crude fiber), C/N ratio, as well as waste reduction efficiency through substrate consumption (SC) and the Waste Reduction Index (WRI). The results showed that food waste contains high levels of protein and carbohydrates, whereas WWTP sludge contains high organic carbon (C-organic). The best feed variation was SML2, producing 27.11% protein, 4.78% fat, and 7.74% crude fiber, indicating its potential as livestock feed. The best frass quality was obtained from SML3 with a C/N ratio of 30.24%, approaching the standard for organic fertilizers. The highest substrate consumption was recorded in SML1 at 58.86%, and the highest WRI reached 5.21%/day. These findings demonstrate that BSF larvae are effective in reducing hospital organic waste while simultaneously producing valuable end products.